Implementation of the Policy on the New Student Admissions Process at Public Middle Schools Zoned in Seberang Ulu Satu District, Palembang City - Nurjanah, Nurjanah; Putra, Alhadi Yan; Djunaidi, Djunaidi (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this study is to understand and analyze the implementation of the new student admission process at SMP Negeri 7 and SMP Negeri 15 Palembang in Seberang Ulu Satu District, Palembang City. The focus of this study is how the New Student Admissions (PPDB) is implemented in accordance with the regulations set by the government, as well as factors that support and hinder its implementation. This study uses a qualitative approach with a case study method. Data were collected by means of observation, documentation, and in-depth interviews, after which a qualitative descriptive analysis was conducted. The results of the study indicate that the implementation of PPDB in both schools is in accordance with the Regulation of the Minister of Education and Culture concerning the zoning system. However, there are still a number of challenges in its implementation, including the lack of public understanding of the zoning system, damage to technological infrastructure, and the presence of outside expertise. Additionally, collaboration between schools and community organizations is crucial. The commitment of school officials and cooperation from the Education Office are the most important factors in carrying out this task. This study shows that the implementation of PPDB at SMP Negeri 7 and 15 Palembang went well, although there is still a need for improvement in the areas of socialization and transparency.